2018
DOI: 10.1111/iej.13048
|View full text |Cite
|
Sign up to set email alerts
|

EDTA conditioning of circumpulpal dentine induces dentinogenic events in pulpotomized miniature swine teeth

Abstract: Aim To investigate pulp responses after pulpotomy and EDTA conditioning of pulp chamber dentinal walls with or without the placement of a collagenous scaffold in the experimental model of miniature swine teeth. Methodology Forty‐two fully developed permanent premolars and molars of healthy miniature swines were used. After preparation of pulp exposures through Class I cavities, the tissue of the pulp chamber was completely removed. The haemorrhage was controlled, and the root pulp was protected using a polyure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additionally, the use of sodium hypochlorite and antibiotic pastes in high concentrations compromised stem cell survival (Ruparel et al , Martin et al ). However, calcium hydroxide was less harmful and EDTA even promoted adhesion, migration and differentiation of pulp stem cells on dentine (Galler et al , Tziafas et al ). Accordingly, the European Society of Endodontology (ESE) released a position statement indicating a clinical protocol for revitalization in 2016 (ESE ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the use of sodium hypochlorite and antibiotic pastes in high concentrations compromised stem cell survival (Ruparel et al , Martin et al ). However, calcium hydroxide was less harmful and EDTA even promoted adhesion, migration and differentiation of pulp stem cells on dentine (Galler et al , Tziafas et al ). Accordingly, the European Society of Endodontology (ESE) released a position statement indicating a clinical protocol for revitalization in 2016 (ESE ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, according to a recent systematic review and meta-analysis, a significant increase in fracture resistance was noted when CEC preparation was performed with preservation of tooth marginal ridges ( Ballester et al, 2021 ). Thus this approach, accompanied by minimal mechanical preparation of root canal walls ( El-Kateb et al, 2020 ), would offer a chance to preserve the coronal tooth structure and maximize the release of growth factors sequestered within the pericervical dentin ( Tziafas et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the preservation of peri-cervical dentin in particular which has an anatomical pattern of a lesser inter-tubular dentin and wider dentinal tubule lumen can justify the evidence of greater sequestered growth factors including TGF-β1, FGF2, and VEGF found in this region ( Tziafas et al, 2019 ; Ferreira et al, 2020 ). This would thus preserve the physiologic and defensive function of dentin which has been proven to have a defensive mechanism that involves the release of pro-inflammatory cytokines and antibacterial agents ( Ayoub et al, 2020 ; Shah et al, 2020 ).…”
Section: Regenerative and Minimally Invasive Endodontic Procedures: T...mentioning
confidence: 99%
“…Although the use of bioactive hard-setting materials such as MTA or Biodentine can provide mineralized tissue formation and good sealing, they cannot allow the penetration of the stem/progenitor cells through the damaged area [10]. On the other hand, a previous study showed that ethylenediaminetetraacetic acid (EDTA) conditioning of the dentin with a collagenous scaffold signi cantly enhanced soft tissue growth with tertiary dentin formation on the exposure site of Class 1 cavities of mini swine permanent teeth [11].…”
Section: Introductionmentioning
confidence: 99%